Ca2+ coding and decoding strategies for the specification of neural and renal precursor cells during development. Issue 2 (March 2016) - Moreau, Marc; Néant, Isabelle; Webb, Sarah E.; Miller, Andrew L.; Riou, Jean-François; Leclerc, Catherine
Graphical abstract: Highlights: Ca 2+ is a second messenger which can direct stem cells towards a specific fate. Comparison of the Ca 2+ signalling events in neural determination and kidney field specification. the transcriptional control of gene expression during neurogenesis and nephrogenesis might be directly controlled by Ca 2+ . Abstract: During embryogenesis, a rise in intracellular Ca 2+ is known to be a widespread trigger for directing stem cells towards a specific tissue fate, but the precise Ca 2+ signalling mechanisms involved in achieving these pleiotropic effects are still poorly understood. In this review, we compare the Ca 2+ signalling events that appear to be one of the first steps in initiating and regulating both neural determination (neural induction) and kidney development (nephrogenesis). We have highlighted the necessary and sufficient role played by Ca 2+ influx and by Ca 2+ transients in the determination and differentiation of pools of neural or renal precursors. We have identified new Ca 2+ target genes involved in neural induction and we showed that the same Ca 2+ early target genes studied are not restricted to neural tissue but are also present in other tissues, principally in the pronephros. In this review, we also described a mechanism whereby the transcriptional control of gene expression during neurogenesis and nephrogenesis might be directly controlled by Ca 2+ signalling. This mechanism involves members of the Kcnip family such that a change in their binding properties to specific DNA sites is a result of Ca 2+ binding to EF-hand motifs. The different functions of Ca 2+ signalling during these two events illustrate the versatility of Ca 2+ as a second messenger.